2001
DOI: 10.1093/sleep/24.6.680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Afternoon “Siesta” Naps on Sleep, Alertness, Performance, and Circadian Rhythms in the Elderly

Abstract: Healthy seniors were able to adopt a napping regimen involving a 90-minute siesta nap each day between 13:30 and 15:00, achieving about one hour of actual sleep per nap. There were some negative consequences for nocturnal sleep in terms of reduced sleep efficiency and earlier waketimes, but also some positive consequences for objective evening performance and (in the diary study) 24-hour sleep totals. Subjective alertness measures and performance measures showed no reliable effects and circadian phase paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
124
4
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 20 publications
10
124
4
2
Order By: Relevance
“…Thus, simply gaining more total sleep time is insufficient to produce memory benefits in older adults. 50 By contrast, our findings are compatible with the view that age-related changes in sleep physiology, cognitive processing, or other relevant underlying neurophysiology preclude an afternoon nap from being as strongly restorative for episodic memory in older adults as in healthy young adults. Regarding sleep-specific mechanisms, if a specific quantity/quality of slow-wave sleep is necessary for any memory consolidation to occur, then no nap duration will benefit older adults' memory if the slow-wave sleep requirement is not met.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, simply gaining more total sleep time is insufficient to produce memory benefits in older adults. 50 By contrast, our findings are compatible with the view that age-related changes in sleep physiology, cognitive processing, or other relevant underlying neurophysiology preclude an afternoon nap from being as strongly restorative for episodic memory in older adults as in healthy young adults. Regarding sleep-specific mechanisms, if a specific quantity/quality of slow-wave sleep is necessary for any memory consolidation to occur, then no nap duration will benefit older adults' memory if the slow-wave sleep requirement is not met.…”
Section: Discussionsupporting
confidence: 86%
“…Because daytime sleep has been shown to increase alertness and improve a range of cognitive functions (perceptual, verbal, and motor learning; declarative and implicit memory) (18,(21)(22)(23)(24), we tested whether sleep or quiet rest might enhance general creativity on new RAT items. Baseline assessments were measured on the morning RAT.…”
Section: Figmentioning
confidence: 99%
“…When assessing healthy elderly without complaints related to nocturnal sleep, authors found that 90 minutes naps between 13h30 and 15h00, established in the study protocol, although it resulted in lower efficiency of nocturnal sleep, it also positively influenced psychomotor performance after the period of the nap (6) .…”
Section: Introductionmentioning
confidence: 99%